The man who sold the world : Ronald Reagan and the betrayal of Main Street America - Kleinknecht, William, 1960- (Nation Books, 2009)
Since Ronald Reagan left office--and particularly after his death--his shadow has loomed large over American politics: Republicans and many Democrats have waxed nostalgic, extolling the Republican tradition he embodied, the optimism he espoused, and his abilities as a communicator. This carefully calibrated image is complete fiction, argues journalist William Kleinknecht. The Reagan presidency was epoch-shattering, but not--as his propagandists would have it--because it invigorated private enterprise or made America feel strong again. His real legacy was the dismantling of an eight-decade period of reform in which working people were given an unprecedented sway over our politics, our economy, and our culture. Reagan halted this almost overnight. Kleinknecht explores middle America--starting with Reagan's hometown of Dixon, Illinois--and shows that as the Reagan legend grows, his true legacy continues to decimate middle America--From publisher description.